2020
DOI: 10.3389/fcimb.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Pathobionts in the Vaginal Microbiota: Individual Participant Data Meta-Analysis of Three Sequencing Studies

Abstract: Having pathobionts was positively associated with young age, non-Dutch origin, hormonal contraceptive use, smoking, antibiotic use in the 14 days prior to sampling, van de Wijgert et al. Pathobionts in the Vaginal MicrobiotaHIV status, and the presence of sexually transmitted pathogens, in at least one but not all studies; inconsistently associated with sexual risk-taking and unusual vaginal discharge reporting; and not associated with vaginal yeasts detection by microscopy. We recommend that future VMB studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
(31 reference statements)
1
33
0
1
Order By: Relevance
“…Of these, CST IV-C1 ( Streptococcus -dominated) and CST IV-C3 ( Bifidobacterium -dominated) were the most common among reproductive age women. The Nugent scoring system was not designed with either of these taxa in mind [ 35 ] and it is not clear how they relate to vaginal health [ 47 ]. While group B Streptococcus is a known neonatal pathogen, it is not known whether its pathogenic potential is at all realized in the vaginal environment [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, CST IV-C1 ( Streptococcus -dominated) and CST IV-C3 ( Bifidobacterium -dominated) were the most common among reproductive age women. The Nugent scoring system was not designed with either of these taxa in mind [ 35 ] and it is not clear how they relate to vaginal health [ 47 ]. While group B Streptococcus is a known neonatal pathogen, it is not known whether its pathogenic potential is at all realized in the vaginal environment [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diseased-state (CST IV) and facilitated-BV state (CST III) vaginal community were more commonly found in sub-Saharan African [ 6 , 10 ]. It is conceivable that genetic factors in these groups may alter the vaginal immune responses which favours the colonisation of L. iners and pathobionts that cause vaginal dysbiosis [ 56 , 57 ]. As has been noted, the characterisation of microbial community in vagina has vastly extended our knowledge on the relationship between healthy and abnormal vaginal microbiota.…”
Section: Indigenous Vaginal Microbiota In Womenmentioning
confidence: 99%
“…A significant decrease in VMB richness (number of species), evenness (relative abundance of each species), and diversity (the overall richness and evenness of species) during pregnancy is associated with PTB ( 43 ). Furthermore, individual vaginal colonization with bacterial pathobionts (symbionts with pathogenic potential, like streptococci, staphylococci, or Enterobacteriaceae species) during pregnancy can associate with adverse pregnancy outcomes ( 44 , 45 ). Son et al ( 46 ) reported that a Klebsiella pneumoniae -dominant VMB might be associated with PTB before 28 weeks of gestational age (GA), Lactobacillus iners with PTB before 34 weeks of GA, and S. agalactiae with late miscarriage ( 46 ).…”
Section: Introductionmentioning
confidence: 99%